FORMATION OF ORGANIZATIONAL AND ECONOMIC INTEGRATED STRUCTURES IN THE ALUMINUM INDUSTRY - S. B. Kazbekova (Модернизация, инновация, развитие)
The paper reveals the theoretical foundations of economic efficiency of production and integrated structures formation. Their advantages are demonstrated by the example of the formation of vertically integrated structures in the aluminium industry in the framework created by smelting aluminium cluster inKazakhstan. Also examines the valuable experience gained in the organization of such structures in theRussian Federationin recent years